Unification of GNSS CORS coordinates in Thailand. Issue 387 (2nd November 2022) - Kriengkraiwasin, Somchai; Charoenphon, Chaiyut; Butwong, Korakod; Kovitpongkajorn, Vichien; Yomwan, Peera; Thongtan, Thayathip; Satirapod, Chalermchon
Abstract : This study estimates station coordinates of GNSS CORS networks in Thailand, based on ITRF2014, by applying the Precise Point Positioning (PPP) technique computed by the GipsyX software. Datum transformation parameters between ITRF2005 and ITRF2014 were investigated to transform station coordinates from ITRF2005 to ITRF2014. The Molodensky-Badekas model provides more reliable results than the Bursa-Wolf model on these transformations. The accuracy of coordinate transformations can be increased by interpolating the remained residuals from transformed coordinates into grid residual corrections. The analyses show that the seven parameters with the grid residual corrections can significantly improve the accuracy of the coordinate transformation.